The Effect of Biological Asset Intensity and Public Share Ownership on Biological Asset Disclosure with Company Growth as a Moderating Variable - Abdullah, Sulthan Yusuf; Purnomo, Budi Supriatono; Heryana, Toni (Universitas Pendidikan Indonesia, 2024)
This study aims to determine the effect of the intensity of biological assets and public ownership of shares on the disclosure of biological assets with company growth as a moderating variable. The research method used is causal research. Sampling used a purposive sampling method in order to obtain a sample of 54 agricultural sector companies listed on the Indonesia Stock Exchange for 2019-2021. In this study using secondary data obtained from annual reports that have been audited by the company. The analytical method used is Multiple Regression Analysis and Moderation Regression Analysis. The test results show that biological assets have a positive effect on the disclosure of biological assets, public ownership has a negative effect on the disclosure of biological assets, company growth does not moderate the effect of the main concern of biological assets on the disclosure of biological assets and company growth moderates the effect of public share ownership on the disclosure of biological assets.